Cultural Terms Negotiation in Indonesian Subtitles of Arabic Netflix Series “Baitu Tahir” and Its Implication for Equivalence at Word Level - Adawiyah, Alfina Robi'ah; Ma'nawi, Arief (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze how cultural identity negotiation occurs in the Indonesian subtitles of the Arabic Netflix series Baitu Tahir and how this process affects word-level equivalence. This study employs a qualitative descriptive approach with subtitling analysis techniques based on Gottlieb’s (1992) translation strategy theory and Baker’s (2018) equivalence theory. Data were collected from three out of six episodes of Baitu Tahir, covering the beginning, middle, and end of the series. The analysis process involved identifying categories of cultural terms (Newmark, 1988) as well as the translation strategies used. Cultural identity negotiation in subtitles impacts word-level equivalence, where some terms are retained, adjusted, or even omitted for readability and audience comprehension. The findings of this study provide insights into how translators navigate the challenges of transferring cultural elements from Arabic to Indonesian in an audiovisual context. This study asserts that subtitle translation is not merely a linguistic process but also a complex form of cultural negotiation. Future research is recommended to expand the scope of data by analyzing more Arabic series from various streaming platforms and exploring how audiences perceive and accept cultural negotiation in subtitles.